(untitled) (Research, Society and Development, 2020)
This work aims to evaluate the modifications of the ISO 9001 version 2015, in relation to its previous version, of 2008, identifying, thus, the necessary steps to implement the changes in an existing Quality Management System in an industrial equipment factory , which does not develop the designs of its manufactured products.